Vulnerability to global warming of a Critically Endangered lizard from the Monte Desert, Patagonia Argentina - Brizio, María Victoria (2021)
The body temperature of lizards is strongly influenced by the thermal quality of microhabitats, exploiting the favourable environmental temperatures, and avoiding exposure to extreme thermal conditions. For these reasons, reptile populations are considered to be especially vulnerable to changes in environmental temperatures produced by climate change. Here, we study the thermal physiology of the critically endangered Añelo Sand Dunes Lizard (Liolaemus cuyumhue Avila, Morando, Perez and Sites, 2009). We hypothesise that (i) there is a thermal coadaptation between optimal temperature for locomotor performance of L. cuyumhue and its thermal preference; (ii) L. cuyumhue lives in an environment with low thermal quality; and (iii) a rise in environmental temperatures due to global warming will impose a decrement in locomotor speed represented by lower warming tolerance and narrower thermal safety margins, increasing their already high vulnerability. We recorded field body temperatures (Tb), preferred body temperatures (Tpref), the operative temperature (Te), and the thermal sensitivity of locomotion at different body temperatures. Our results indicate that this lizard is not currently under environmental stress or exceeding its thermal limits, but that it is thermoregulating below Tpref to avoid overheating, and that an increase in environmental temperature higher than 3.5 °C will strongly affect the use of microhabitats with direct sun exposure.